Transformasi Pendidikan Bahasa Arab Melalui NAFIRA (Nahdlatul Raghibin Fii Lughatil Arabiyah) sebagai Program Unggulan di Pondok Pesantren Darussalam Jombang: Memperbarui Pendidikan Bahasa Arab Melalui NAFIRA (Nahdlatul Raghibin Fii Lughatil Arabiyah) sebagai Program Unggulan - Umirul Musyarofah; Devi Rofidah Celine; Firdaus Ulul Absor; Naila Nafahatus Sahariyah Al-Ulya; M. Yunus Abu Bakar (Language Development Center, 2025)
Background: Improving Arabic language competence in Islamic boarding schools requires innovative and adaptive curriculum models that address students' diverse needs. Purpose: This study aims to analyze the implementation of the NAFIRA program (Nadhirotul Raghibin Fii Lughatil Arabiyah) as an adaptive curriculum innovation to improve students’ Arabic language competence in Darussalam Islamic boarding schools (pesantren). Method: The research employed a qualitative-descriptive method using a case study approach in a pesantren implementing the NAFIRA program. Data were collected through in-depth interviews, direct observations, and document analysis. The population consisted of teachers and students involved in the program, with selected participants as the research sample. Data analysis was conducted through data reduction, data display, and drawing conclusions based on the Miles and Huberman model. Results and Discussion: The results show that NAFIRA is tailored to students’ real language needs and their diverse linguistic backgrounds. The program is implemented through structured planning, teacher training, regular evaluations, and daily monitoring. It has proven effective in developing all four Arabic skills listening, speaking, reading, and writing and has strengthened students’ comprehension of Islamic subjects. The study fills a gap in curriculum research by emphasizing the role of adaptive, need-based program design in Islamic education settings. Conclusions and Implications: NAFIRA has demonstrated its value as an effective, contextual curriculum model for Arabic language education in pesantren. The findings suggest that future curriculum development should prioritize contextual, need-based approaches to improve educational outcomes in Islamic schools. Keyword :NAFIRA, adaptive curriculum, Arabic language, pesantren, educational management